Direct medical costs for patients with type 2 diabetes in 16 tertiary hospitals in urban China: A multicenter prospective cohort study. Issue 2 (5th September 2018) - Li, Xiang; Xu, Zhangrong; Ji, Linong; Guo, Lixin; Liu, Jing; Feng, Kun; Xu, Yushan; Zhu, Dalong; Jia, Weiping; Ran, XinWu; Chen, Limin; Zhao, Shi; et al.
Abstract: Aims/Introduction: To investigate the direct medical costs for patients with type 2 diabetes in China and to examine the influencing factors. Materials and Methods: In the present multicenter study, 1, 070 patients with type 2 diabetes from 16 tertiary hospitals in 14 major cities of China were enrolled. Patient data and direct medical costs were collected during a follow‐up period of 6 months at intervals of 1 month. The log‐transformed direct medical costs were fitted by a generalized estimation equation to indicator variables for demographics, metabolic control, treatments, complications and comorbidities. Results: Data of 871 participants were included in the analysis. The mean annual total direct medical costs and outpatient medical costs were $1, 990.20 and $1, 687.20 respectively. The average costs per inpatient per admission were $2, 127.10. The share of out‐of‐pocket for total medical costs, outpatient costs and cost per inpatient per admission were 45.4, 46.3 and 26.0% respectively. Independent determinants of total medical costs were diabetes duration, dyslipidemia and diabetic complications, such as neuropathy and nephropathy, as well as diabetes treatment, such as the use of glucagon‐like peptide‐1 receptor agonists. Costs showed prominent variation across centers. Conclusions: Diabetes is imposing a growing economic burden in patients with type 2 diabetes in China. Diabetes‐related complications and comorbidities have a great impact on the medical costs. As different health policies, economic development and regional health inequalities also have an important influence on the direct medical cost, healthcare reform needs to optimize resource allocation in health service delivery systems, and provide more equitable and affordable healthcare.